2022
DOI: 10.1002/alz.12630
|View full text |Cite
|
Sign up to set email alerts
|

Identifying best practices for disclosure of amyloid imaging results: A randomized controlled trial

Abstract: Introduction: Empirical studies on effective communication for amyloid disclosure in mild cognitive impairment (MCI) are lacking. We aimed to study the impact of six communication strategies. Method:We performed a randomized controlled trial with seven randomly assigned, video-vignette conditions: six emphasizing a communication strategy and one basic condition. All showed a scripted consultation of a neurologist disclosing positive amyloid positron emission tomography (PET) scan results to an MCI patient. Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 68 publications
(159 reference statements)
0
11
0
Order By: Relevance
“…In addition, although the number of participants with SCD+ who were accompanied by a study partner was very small, we can speculate that these individuals were more sensitive to the disclosure of positive biomarker results or might have been more distressed by the worry of how this information may change their families’ and friends’ perceptions of them than participants with SCD+ without study partners. Concerning risk communication, a recent study found that the use of some communication strategies might maximize the information uptake in mild cognitive impairment patients, thus resulting in higher trust and satisfaction …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, although the number of participants with SCD+ who were accompanied by a study partner was very small, we can speculate that these individuals were more sensitive to the disclosure of positive biomarker results or might have been more distressed by the worry of how this information may change their families’ and friends’ perceptions of them than participants with SCD+ without study partners. Concerning risk communication, a recent study found that the use of some communication strategies might maximize the information uptake in mild cognitive impairment patients, thus resulting in higher trust and satisfaction …”
Section: Discussionmentioning
confidence: 99%
“…Concerning risk communication, a recent study found that the use of some communication strategies might maximize the information uptake in mild cognitive impairment patients, thus resulting in higher trust and satisfaction. 35 Delivering bad news to cognitively unimpaired patients could be one of the most challenging tasks physicians have to face in their clinical practice. Therefore, it is crucial to highlight that disclosing a positive amyloid-PET result was not associated with a clinically relevant psychological change.…”
Section: Jama Network Open | Neurologymentioning
confidence: 99%
“…In a first attempt to empirically derive best practices for disclosure of a positive amyloid PET scan to patients with mild cognitive impairment, we conducted a large randomized controlled study using a video‐vignette design (task 4.3). The resulting paper showed that risk communication best practices, actively attending to emotions, and the teach‐back technique enhance information recall of amyloid PET results and/or could contribute to positive evaluations of the clinician and the provided care 25 …”
Section: Current State Of Aboardmentioning
confidence: 99%
“…While various groups, including the Advisory Group on Risk Evidence Education in Dementia (AGREED), 29 have begun to develop approaches and share resources, a unified and funded effort will be important to fully realize this goal. Researchers may follow the example of prior work on the development of practice guidelines for genetic disclosure in clinical trials 30 as well as ongoing work in investigating and developing optimal communication strategies and personalized biomarker result tools 31–33 …”
Section: Recommendationsmentioning
confidence: 99%